Early Detection of Dengue Virus by Use of Reverse Transcription-Recombinase Polymerase Amplification - Teoh, B.T.; Sam, Sing Sin; Tan, K.K.; Danlami, M.B.; Shu, M.H.; Johari, Jefree; Hooi, P.S.; Brooks, D.; Piepenburg, O.; Nentwich, O.; Wilder-Smith, A.; Franco, L.; et al. (American Society for Microbiology, 2015)
A method for the rapid diagnosis of early dengue virus (DENV) infection is highly needed. Here, a prototype reverse transcriptionrecombinase polymerase amplification (RT-RPA) assay was developed. The assay detected DENV RNA in <20 min without the need for thermocycling amplification. The assay enabled the detection of as few as 10 copies of DENV RNA. The designed RT-RPA primers and exo probe detected the DENV genome of at least 12 genotypes of DENV circulating globally without crossreacting with other arboviruses. We assessed the diagnostic performance of the RT-RPA assay for the detection of DENV RNA in 203 serum samples of patients with clinically suspected dengue. The sera were simultaneously tested for DENV using a reverse transcription-loop-mediated isothermal amplification (RT-LAMP) assay, quantitative RT-PCR (qRT-PCR), and IgM- and IgGcapture enzyme-linked immunosorbent assays (ELISA). Acute DENV infection was confirmed in 130 samples and 61 of the samples (46.9%) were classified as viremic with qRT-PCR. The RT-RPA assay showed good concordance (κ of ≥0.723) with the RTLAMP and qRT-PCR assays in detecting the dengue viremic samples. When used in combination with ELISA, both the RT-RPA and RT-LAMP assays increased the detection of acute DENV infection to ≥95.7% (≥45/47) in samples obtained within 5 days of illness. The results from the study suggest that the RT-RPA assay is the most rapid molecular diagnostic tool available for the detection of DENV. Hence, it is possible to use the RT-RPA assay in a laboratory to complement routine serology testing for dengue.